(untitled) (Research, Society and Development, 2021)
Anadenanthera colubrina var. cebil (Griseb.) Altschul, a plant often found in areas of the Caatinga in northeastern Brazil, is widely used in unconventional medicine for the treatment of infections and inflammations. Thus, the aim of the present study was to evaluate the antibacterial activity of A. colubrina bark extracts against methicillin-resistant Staphylococcus aureus (MRSA) clinical isolates, to investigate if intact and regenerated bark extracts have the same effect against MRSA and to determine the interaction between these extracts and antibiotics. The antibacterial activity was performed by the determination of the minimum inhibitory concentration (MIC) according to the Clinical and Laboratory Standards Institute (CLSI) and the interaction assay was performed by the checkerboard method. A. colubrina extracts showed bacteriostatic activity (MIC = 8-32 mg/L) against MRSA clinical strains and no difference was found in antibacterial activity between intact and regenerated barks, suggesting that even after regeneration, the barks of this species have the same antibacterial activity. Moreover, the in vitro interaction of A. colubrina extracts with ciprofloxacin or erythromycin was additive (FICI = 0.52). Thus, the bark extracts of Anadenanthera colubrina exhibit antibacterial activity and can be used alone or in combination with antibiotics against MRSA clinical isolates.